Australians Can Adopt Mediterranean Diet (MedDiet) Principles up to 1-Year Following Completion of the Medley Trial (OR22-01-19). (13th June 2019) - Murphy, Karen; Dyer, Kathryn; Hyde, Belinda; Davis, Courtney; Hodgson, Jonathan; Woodman, Richard
Abstract: Objectives: Mediterranean populations have enjoyed the health benefits of a Mediterranean diet (MedDiet), for years, which could offer better health to Western countries which suffer from chronic disease such as heart disease. But is it feasible to implement such a pattern beyond the Mediterranean basin? The MedLey trial, a 6 month MedDiet intervention vs habitual diet in older Australians, demonstrated participants could maintain high adherence to a MedDiet for 6 months. The MedDiet resulted in improved systolic blood pressure, endothelial dilatation, oxidative stress and plasma triglycerides in comparison with habitual diet (control). The objective of the present study was to follow participants for an additional 12 months post-completion of the MedLey trial in order to assess MedDiet adherence, blood pressure (BP), BMI and triglycerides. Methods: Participants completed a food frequency questionnaire and a 15-point MedDiet adherence score (MDAS; greater score = greater adherence) was calculated. Home BP was measured over 6 days, BMI was assessed and fasting plasma triglycerides were measured. Data were analysed using intention-to-treat LMEM with a group x time interaction term comparing data at baseline and 4 and 18-months (12-months post-trial). Results: At 18-months, the MedDiet group had a MDAS of 7.9 ± 0.3, compared to 9.6 ± 0.2 at 4 months ( P  < 0.0001), and 6.7 ± 0.2 ( P  < 0.0001), at baseline. The MDAS in the HabDiet group remained unchanged over the 18 month period. Consumption of olive oil, legumes, fish and vegetables ( P  < .01) remained higher and discretionary food consumption ( P  = .02) remained lower at 18 months than baseline levels in the MedDiet group. There was no difference between baseline and 18 months for the HabDiet. Blood pressure, BMI and triglycerides were not significantly different to baseline in either group. Conclusions: These data show some MedDiet principles could be adhered to for 1-year after finishing the MedLey trial. However improvements in cardiometabolic health markers were not sustained, indicating further dietary support may be beneficial to maintain high adherence. Funding Sources: The MedLey Trial was supported by a grant from the National Health & Medical Research Council Project Grant.